Recent Advances in Research on Molecular Mechanisms of Fungal Signaling - Stefan Jacob; Sri Bühring; Katharina Bersching (Encyclopedia, 2022)
Biochemical signaling is one of the key mechanisms to coordinate a living organism in all aspects of its life. It is still enigmatic how exactly cells and organisms deal with environmental signals and irritations precisely because of the limited number of signaling proteins and a multitude of transitions inside and outside the cell. Many components of signaling pathways are functionally pleiotropic, which means they have several functions. A single stimulus often results in multiple responses, a distinct response can be triggered by numerous stimuli and signals initiated by different stimuli are often transduced via commonly used network components. This review sheds light on the most important molecular mechanisms of cellular signaling in fungi and consequently provides a comprehensive overview about the current state of research on the road to understand the impact of signal transduction in eukaryotic microorganisms.